Mitochondrial function assessed by 31P MRS and BOLD MRI in non‐obese type 2 diabetic rats. Issue 15 (10th August 2016) - Liu, Yuchi; Mei, Xunbai; Li, Jielei; Lai, Nicola; Yu, Xin
Abstract: The study aims to characterize age‐associated changes in skeletal muscle bioenergetics by evaluating the response to ischemia‐reperfusion in the skeletal muscle of the Goto‐Kakizaki (GK) rats, a rat model of non‐obese type 2 diabetes (T2D). 31 P magnetic resonance spectroscopy (MRS) and blood oxygen level‐dependent (BOLD) MRI was performed on the hindlimb of young (12 weeks) and adult (20 weeks) GK and Wistar (control) rats. 31 P‐MRS and BOLD‐MRI data were acquired continuously during an ischemia and reperfusion protocol to quantify changes in phosphate metabolites and muscle oxygenation. The time constant of phosphocreatine recovery, an index of mitochondrial oxidative capacity, was not statistically different between GK rats (60.8 ± 13.9 sec in young group, 83.7 ± 13.0 sec in adult group) and their age‐matched controls (62.4 ± 11.6 sec in young group, 77.5 ± 7.1 sec in adult group). During ischemia, baseline‐normalized BOLD‐MRI signal was significantly lower in GK rats than in their age‐matched controls. These results suggest that insulin resistance leads to alterations in tissue metabolism without impaired mitochondrial oxidative capacity in GK rats. Abstract : The current study aimed at delineating the development of metabolic abnormalities in the skeletal muscle of non‐obese, insulin resistant rats. Mitochondrial function and muscle oxygenation in response to ischemia‐reperfusion were assessed by magnetic resonance spectroscopy and imaging. The results suggest that insulin resistance leads to alterations in tissue metabolism without impaired mitochondrial oxidative capacity in insulin‐resistant rats.